Blockading Britain and Germany during World War 1: preparations, conduct and consequence of economic warfare - Broadberry, S; Vonyó, T (University of Oxford, 2025)
A pre-war policy of free trade in Britain and protection in Germany meant that Britain entered the war producing 35 per cent of its food needs while Germany produced 80 per cent. And yet Britain managed to feed itself adequately while Germany faced food shortages. Britain successfully adopted a range of counter-measures, exhibiting a capacity for substitution, allowing the economy to be flexible enough to survive the German blockade. The blockade accounted for at most around a quarter of the decline in German food consumption, which was largely the result of a collapse in domestic production caused by excessive mobilisation. German counter-measures were sometimes successful, but at other times indicate a less flexible economy with a limited capacity for substitution. The British government quickly reversed wartime policies to boost agricultural production and entered World War 2 equally vulnerable to submarine blockade, while Germany pursued autarkic policies to avoid dependence on seaborne imports.